2017
DOI: 10.1016/j.mce.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma antigen-A11 regulates substrate-specificity of Skp2-mediated protein degradation

Abstract: Melanoma antigen-A11 (MAGE-A11) is a proto-oncogene involved in androgen receptor signaling and androgen-dependent cell growth. In this report we provide evidence that MAGE-A11 interacts with Skp2 (S phase kinase-associated protein), the substrate recognition protein of the Skp1-Cullin1-F-box E3 ubiquitin ligase, and with Skp2 binding protein, cyclin A. A similar cyclin A binding motif in MAGE-A11 and Skp2 was consistent with a competitive relationship between MAGE-A11 and Skp2 in binding cyclin A. Skp2 inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…However, it does not affect p53 turnover mediated by MDM2 [ 36 ]. MAGE-A11 interacts with Skp2, the substrate recognition protein of the Skp1-Cullin1-F-box E3 ubiquitin ligase, and increases Skp2-mediated degradation of cyclin A and p130, but decreases Skp2-mediated degradation of E2F1 and Skp2 self-ubiquitination by sequestering and inactivating Skp2 via forming an E2F1-MAGE-A11-Skp2 complex [ 37 ].…”
Section: Biological Functions Of Mages In Cancer Progressionmentioning
confidence: 99%
“…However, it does not affect p53 turnover mediated by MDM2 [ 36 ]. MAGE-A11 interacts with Skp2, the substrate recognition protein of the Skp1-Cullin1-F-box E3 ubiquitin ligase, and increases Skp2-mediated degradation of cyclin A and p130, but decreases Skp2-mediated degradation of E2F1 and Skp2 self-ubiquitination by sequestering and inactivating Skp2 via forming an E2F1-MAGE-A11-Skp2 complex [ 37 ].…”
Section: Biological Functions Of Mages In Cancer Progressionmentioning
confidence: 99%
“…In addition, MAGEs have been reported to alter substrate specificity of ligases, such that MRL complexes have a different spectrum of targets than the E3 RING alone. Mechanistically MAGE proteins can directly bind substrates and recruit them to the E3 ligase for ubiquitination, such as MAGE-A3/6 binding AMPK and mediating its ubiquitination by TRIM28 (25) or change substrate preference in the case of MAGE-A11 and Skp2 (35). Also, MAGEs can alter the subcellular localization of the ligase allowing it to find novel substrates, such as MAGEL2 directing TRIM27 to endosomes for ubiquitination WASH (26).…”
Section: Mage-ring Ligases (Mrls)mentioning
confidence: 99%
“…A subsequent study found that MAGE-A11 interacts with Skp2, an F-box domain substrate recognition protein of the SCF CRL [53]. In this case, MAGE-A11 regulates substrate specificity of Skp2, such that MAGE-A11 enhances Skp2-mediated degradation of cyclin A and the retinoblastoma-related protein p130, but inhibits Skp2-mediated degradation of the E2F1 transcription factor [53].…”
Section: Function and Mechansim Of Mage-ring Ligasesmentioning
confidence: 99%
“…In this case, MAGE-A11 regulates substrate specificity of Skp2, such that MAGE-A11 enhances Skp2-mediated degradation of cyclin A and the retinoblastoma-related protein p130, but inhibits Skp2-mediated degradation of the E2F1 transcription factor [53]. The authors account the differential effects of MAGE-A11 on Skp2 by proposing a competitive relationship between MAGE-A11 and Skp2 in binding cyclin A [53]. Collectively these data suggest that MAGEs may regulate cell cycle progression by modulating SCF ubiquitin ligase activity and substrate recognition.…”
Section: Function and Mechansim Of Mage-ring Ligasesmentioning
confidence: 99%